Metformin Clinical Trial in HPV+ and HPV– Head and Neck Squamous Cell Carcinoma: Impact on Cancer Cell Apoptosis and Immune Infiltrate - Curry, Joseph M.; Johnson, Jennifer; Mollaee, Mehri; Tassone, Patrick; Amin, Dev; Knops, Alexander; Whitaker-Menezes, Diana; Mahoney, My G.; South, Andrew; Rodeck, Ulrich; Zhan, Tingting; Harshyne, Larry; et al. (Frontiers in Oncology, 2018)
Background: Metformin, an oral anti-hyperglycemic drug which inhibits mitochondrial complex I and oxidative phosphorylation has been reported to correlate with improved outcomes in head and neck squamous cell carcinoma (HNSCC) and other cancers. This effect is postulated to occur through disruption of tumor-driven metabolic and immune dysregulation in the tumor microenvironment (TME). We report new findings on the impact of metformin on the tumor and immune elements of the TME from a clinical trial of metformin in HNSCC. Methods: Human papilloma virus—(HPV–) tobacco+ mucosal HNSCC samples (n = 12) were compared to HPV+ oropharyngeal squamous cell carcinoma (OPSCC) samples (n = 17) from patients enrolled in a clinical trial. Apoptosis in tumor samples pre- and post-treatment with metformin was compared by deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay. Metastatic lymph nodes with extra-capsular extension (ECE) in metformin-treated patients (n = 7) were compared to archival lymph node samples with ECE (n = 11) for differences in immune markers quantified by digital image analysis using co-localization and nuclear algorithms (PD-L1, FoxP3, CD163, CD8). Results: HPV–, tobacco + HNSCC (mean Δ 13.7/high power field) specimens had a significantly higher increase in apoptosis compared to HPV+ OPSCC specimens (mean Δ 5.7/high power field) (p < 0.001). Analysis of the stroma at the invasive front in ECE nodal specimens from both HPV—HNSCC and HPV+ OPSCC metformin treated specimens showed increased CD8+ effector T cell infiltrate (mean 22.8%) compared to archival specimens (mean 10.7%) (p = 0.006). Similarly, metformin treated specimens showed an increased FoxP3+ regulatory T cell infiltrate (mean 9%) compared to non-treated archival specimens (mean 5%) (p = 0.019). Conclusions: This study presents novel data demonstrating that metformin differentially impacts HNSCC subtypes with greater apoptosis in HPV—HNSCC compared to HPV+ OPSCC. Moreover, we present the first in vivo human evidence that metformin may also trigger increased CD8+ Teff and FoxP3+ Tregs in the TME, suggesting an immunomodulatory effect in HNSCC. Further research is necessary to assess the effect of metformin on the TME of HNSCC.